A corotational triangular facet shell element for geometrically nonlinear analysis of thin piezoactuated structures. (15th July 2017) - Bisegna, Paolo; Caruso, Giovanni; Caselli, Federica; Nodargi, Nicola A.
Abstract: A simple and effective corotational triangular facet shell finite element is proposed for the geometric nonlinear analysis of thin piezoactuated structures. The structures under investigation are laminated shells composed of elastic layers and sensory/active piezoelectric layers, perfectly bonded to each other. A polar decomposition based corotational framework is adopted. By filtering out large rigid body motions from structural displacements, this framework allows (i) to account for arbitrarily large displacements/rotations, provided strains are small, and (ii) to use existing and high-performance linear elements as core-elements. Within the classical laminated plate theory, the small strain core element formulation based on superposition of OPT membrane and DKT plate element is used, along with a layer-wise constant interpolation of the transversal component of the electric field. Numerical simulations dealing with benchmark problems and applications of technological interest prove accuracy and effectiveness of the proposed formulation.